2016
DOI: 10.1186/s12957-016-1056-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of COL1A1 and COL1A2 as candidate prognostic factors in gastric cancer

Abstract: BackgroundThe role of type I collagen, composed of collagen type I alpha 1 (COL1A1) and collagen type I alpha 2 (COL1A2), has been studied in several cancers. However, the expression of COL1A1 and COL1A2 in malignant, premalignant, and normal gastric tissues and their clinical significances in gastric cancer have not been elucidated.MethodsReal-time quantitative PCR was performed in 55 malignant, 27 premalignant, and 19 normal tissues to measure COL1A1 and COL1A2 messenger RNA (mRNA) expression, and the correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 23 publications
(25 reference statements)
8
123
0
Order By: Relevance
“…Disruption in collagen metabolism causes progression of osteoarthritis, osteoporosis, and oncogenesis . Interestingly, the genes involved in this study were the key structural components of ECM . ECM contains multiple proteins including collagens, laminin, fibronectin, hyaluronan and proteoglycan .…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Disruption in collagen metabolism causes progression of osteoarthritis, osteoporosis, and oncogenesis . Interestingly, the genes involved in this study were the key structural components of ECM . ECM contains multiple proteins including collagens, laminin, fibronectin, hyaluronan and proteoglycan .…”
Section: Discussionmentioning
confidence: 78%
“…Collagen is the dominant structural component of connective tissue, which maintains the stability of organs and supports structural integrity . These collagens are the key structural components of ECM . We then validated the RNA expression of these four candidate genes in our dataset.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…COL1A1 encodes the subunit of type I collagen, which is preferentially synthesized in the bone, dermis, and tendons [24], and is recognized as a tumor-related gene. Previous studies reported that COL1A1 is upregulated in the tumor tissues in breast, gastric and liver cancers, and most likely participates in tumorigenesis [25][26][27]. Thus, the mis-splicing of COL1A1 may play a potential role in LSCC tumorigenesis.…”
Section: Evaluation Of the Target Mirnas Of Hsa_circ_0044520 And Hsa_mentioning
confidence: 96%